A Case of Severe Asthma with Eosinophilic Otitis Media Successfully Treated with Anti-IgE Monoclonal Antibody Omalizumab - Azusa Okude; Etsuko Tagaya; Mitsuko Kondo; Manabu Nonaka; Jun Tamaoki (Case Reports in Pulmonology)
A 51-year-old woman had been receiving medical treatment for asthma since she was 21 years old. However, her asthma was poorly controlled despite treatment involving combination inhalation of high-dose corticosteroid and long-acting β2-aderenergic agonist (LABA) and regularly taking oral steroids. Hearing loss and otorrhea appeared at the age of 44, and she was given a diagnosis of eosinophilic otitis media (EOM) and received medical treatment. In 2007, symptoms of asthma and otitis media deteriorated. In December 2009, omalizumab therapy was started for refractory asthma. After 2 months of omalizumab treatment, not only asthma, but also hearing loss improved. It is suggested that early initiation of omalizumab therapy may inhibit the progression of progressive EOM.